2016
DOI: 10.1016/j.ijsu.2016.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Challenging situations in partial nephrectomy

Abstract: Although most partial nephrectomies are performed as primary procedures in the elective or semi-imperative setting on kidneys with relatively normal anatomy, this is not always the case.The indications for partial nephrectomy continue to expand and it is becoming particularly relevant in patients with single functioning kidneys, poor kidney function, anatomical anomalies and hereditary syndromes predisposing to multiple kidney cancers, such as Von Hippel-Lindau syndrome. These, along with previous abdominal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Approximately 75% of renal masses are less than 4 cm in size was detected incidentally [13]. By the advances in renal and vascular surgery; partial nephrectomy (PN) is now considered the standard treatment that has superior functional and equivalent oncological outcomes for T1 tumors (<7 cm) when techniqually feasible [14]. The first case of open partial nephrectomy (OPN) for renal tumor was performed by Czerny in 1887 [15].…”
Section: Surgery Of Kıdney Cancermentioning
confidence: 99%
“…Approximately 75% of renal masses are less than 4 cm in size was detected incidentally [13]. By the advances in renal and vascular surgery; partial nephrectomy (PN) is now considered the standard treatment that has superior functional and equivalent oncological outcomes for T1 tumors (<7 cm) when techniqually feasible [14]. The first case of open partial nephrectomy (OPN) for renal tumor was performed by Czerny in 1887 [15].…”
Section: Surgery Of Kıdney Cancermentioning
confidence: 99%
“…To round off the special series, Raison et al [15] cover particularly challenging and unusual situations in partial nephrectomy that a urologist may encounter M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 and Caputo et al [16] discus how to deal with the complications arising from the procedure.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…A tumor in a horseshoe kidney is considered one of the most challenging circumstances, even in experienced hands. 6 We herein present a case of renal cell carcinoma (RCC) within a horseshoe kidney near the isthmus with a complicated blood supply treated by LPN. According to our online literature review, few such cases have been reported to date.…”
Section: Introductionmentioning
confidence: 99%